The Effect of Charades Game Towards Students’ Vocabulary Mastery At The Eighth Grade Students Of Mts Mathla’ul Anwar Binuangeun Wanasalam Lebak-Banten in Academic Year 2023/2024 - Agi Sundari (Riviera Publishing, 2024)
These skills are supported by learning elements such as structure, vocabulary, pronunciation, grammar, and spelling. One of them is vocabulary, vocabulary is also a language component that plays an important role in language learning. This research paper aims to determine The Effect of Charades Game Towards Students’ Vocabulary Mastery at the Eighth Grade Students of MTs Mathla’ul Anwar Binuangeun Wanasalam Lebak-banten. This study uses a quantitative approach with a quasi-experimental design research method, which uses three concepts, namely, pre-test, treatment and post-test. The population was 144 students and the samples of this research was 72 students that consisted of 36 students of experimental class and 36 students of control class. The result of post-test both experimental class and control class, after getting the treatment the result of experimental class 65.83 and control class is 62,08, it means the result of experimental class is higher than control class. Based on the data above, the charades game showed better results in the experimental class than the control class.